Mecanismos de morte celular induzida pela radiação Y e expressão de proteínas nas novas linhagens de câncer de mama humano MACL-1 e MGSO-3 - Caryne Margotto Bertollo (2010)
Cancer represents a major cause of death worldwide. It is estimated that in 2008 7.6 million people died as a consequence of this disease. In Brazil, breast cancer is the second most common type of cancer and 49 000 new cases are expected in 2010. The diagnosis and treatment of this cancer remain as challenges. The characterization of new cell lines is an important tool to understand the biological processes involved in cancer treatments. In the present study we used two newly established epithelial human breast cancer cell lines from primary sites MACL-1 and MGSO-3 and compared their susceptibility to the treatment with ionizing radiation (IR) with the commercial cell line MDA-MB-231. In the doses used (10 or 20 Gy), IR induced a reduction in cell viability and cell death, measured as DNA fragmentation, at 48 and 72 h after treatment. In addition, 48 h after treatment with IR we observed an enhancement in the percentage of apoptotic cells. The broad-range caspases inhibitor zVAD-FMK inhibited IR cytotoxicity, suggesting the involvement of caspases in cell death induced by this treatment. After 24h, treatment with IR activated caspase-9 in MACL-1 and MDA-MB-231 but not in MGSO-3 cells. Thirty hours after treatment with IR (20 Gy), we observed an activation of caspases 8 and 3. Although it was shown that IR induces cytotoxicity no alterations were detected in protein expression, assessed by two-dimensional electrophoresis, 24 or 30 h after treatment of MDA-MB-231 with 20 Gy. Through two-dimensional electrophoresis and mass spectrometry it was shown that there are differences in protein expression profile of strains MACL-1 and MGSO-3 when compared to cells obtained from healthy breast tissue. Together, these results suggest that the newly established human breast cancer cell lines, MACL-1 and MGSO-3, may be useful in studies of breast cancer in defining basic mechanisms in molecular and cellular radiobiology and may contribute to the rational design of future models of cancer therapies as well as the identification of markers for this type of cancer.